Developing CT based computational models of pediatric femurs. Issue 10 (16th July 2015) - Li, Xinshan; Viceconti, Marco; Cohen, Marta C.; Reilly, Gwendolen C.; Carré, Matt J.; Offiah, Amaka C.
Abstract: The mechanisms of fracture in infants and toddlers are not well understood. There have been very few studies on the mechanical properties of pediatric bones and their responses under fracture loading. A better understanding of fracture mechanisms in children will help elucidate both accidental and non-accidental injuries, as well as bone fragility diseases. The aim of this study is to develop in silico femoral models from CT scans to provide detailed quantitative information regarding the geometry and mechanical response of the femur, with the long term potential of investigating injury mechanisms. Fifteen anonymized QCT scans (aged 0–3 years) were collected and used to create personalized computational models of femurs. The elastic modulus of femur was illustrated at various ages. The models were also subjected to a series of four point bending simulations taking into account a range of loads perpendicular to the femoral shaft. The results showed that mid-shaft cross-section at birth appeared circular, but the diameter in the anteroposterior axis gradually increased with age. The density, and by implication modulus of elasticity at the mid-shaft became more differentiated with growth. Pediatric cortical bone with density close to the peak values found in adults was attained a few weeks after birth. The method is able to capture quantitative variations in geometries, material properties and mechanical responses, and has confirmed the rapid development of bone during the first few years of life using in silico models.